PUBLIC AUTHORITIES AS SUBJECTS OF LEGAL RELATIONS IN THE FIELD OF CHILD PROTECTION DURING ARMED CONFLICTS - Chepkova, K. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2022)
The article analyzes the issue of competence of state authorities as subjects of legal relations in the field of child protection during armed conflicts. Based on the functional division of state power, the author considered the structure of state authorities in the field of child protection during armed conflicts. Thus, the author stated that the only body of legislative power in Ukraine is the parliament – Verkhovna Rada of Ukraine. According to the Constitution of Ukraine, the foundations of social protection, childhood protection, upbringing, education, culture and health care are determined exclusively by the laws of Ukraine. The executive branch of government is represented by a number of state authorities. First of all, it is the Cabinet of Ministers of Ukraine. Based on the functional approach, a four-level system of central executive authorities in the field of child protection during armed conflicts is proposed, which includes: Level I – Cabinet of Ministers of Ukraine; Level II – ministries of Ukraine (Ministry of Social Policy, Ministry of Reintegration of Temporarily Occupied Territories); Level III – state services, state inspections, state agencies, independent regulators and bodies with special status (National Social Service Service); IV level – local state administrations. The author also analyzed the system of control and supervisory bodies in the field of child protection during armed conflicts. There are the Ukrainian Parliament Comissioner for Human Rights and the Authorized Adviser to the President of Ukraine on Children’s Rights and Child. It is pointed out that there is no normative legal act that would regulate the issues and scope of activity of the Adviser Authorized President of Ukraine on Children’s Rights and Child Rehabilitation, which in practice may lead to duplication and inconsistency of actions with other state institutions in the field of child protection during armed conflicts. Attention has been drawn to the tendency to create a number of consultative and advisory bodies whose competence includes the protection of children during armed conflicts, namely the Coordination Headquarters for the Protection of Children’s Rights in Martial Law and the National Council of Ukraine for the Recovery of Ukraine from the Consequences of War, which is consultative advisory body under the President of Ukraine.